PPARγ Mediates the Anti-Epithelial-Mesenchymal Transition Effects of FGF1ΔHBS in Chronic Kidney Diseases via Inhibition of TGF-β1/SMAD3 Signaling - Wang, Dezhong; Zhao, Tianyang; Zhao, Yushuo; Yin, Yuan; Huang, Yuli; Cheng, Zizhao; Wang, Beibei; Liu, Sidan; Pan, Minling; Sun, Difei; Wang, Zengshou; Zhu, Guanghui (Frontiers in Pharmacology, 2021)
Podocytes are essential components of the glomerular basement membrane. Epithelial-mesenchymal-transition (EMT) in podocytes results in proteinuria. Fibroblast growth factor 1 (FGF1) protects renal function against diabetic nephropathy (DN). In the present study, we showed that treatment with an FGF1 variant with decreased mitogenic potency (FGF1ΔHBS) inhibited podocyte EMT, depletion, renal fibrosis, and preserved renal function in two nephropathy models. Mechanistic studies revealed that the inhibitory effects of FGF1ΔHBS podocyte EMT were mediated by decreased expression of transforming growth factor β1 via upregulation of PPARγ. FGF1ΔHBS enhanced the interaction between PPARγ and SMAD3 and suppressed SMAD3 nuclei translocation. We found that the anti-EMT activities of FGF1ΔHBS were independent of glucose-lowering effects. These findings expand the potential uses of FGF1ΔHBS in the treatment of diseases associated with EMT.